Detection Suspicious Activities on Network Package Traffic - Kustian, Nunu; Ilham Tantowi, Anggit; ., Herlinda; Parulian, Dudi; Windia Ambarsari, Erlin (KnE Social Sciences, 2023)
One problem of computer network security was that unauthorized people had access to websites on the internet—the way to interject malicious programs that aim to send viruses and even commit data theft. Therefore, it was critical to understand the types of attacks in the different forms of crime that can not only harm organizational infrastructure but also affect financially. Detection of criminal activities was carried out with the help of Wireshark Software to view data packets, which indicated criminal programs carried out by intruders secretly on the official website. The capture packets on the running network had suspicious packets as evidence that led to malware infections. Therefore, both the owner and website users needed security protection by planning strategies to overcome criminal activities that infect websites. Keywords: malicious programs, malware, network package traffic, Wireshark